1993
DOI: 10.1017/s0021859600074311
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress during mid-pregnancy in sheep and the consequences for placental and fetal growth

Abstract: SUMMARYAn experiment was conducted at Toorak Research Station, Julia Creek, in semi-arid northern Australia (141° E, 21° S) during 1990 to determine the relationship between placental and fetal weight in sheep after placental growth had been restricted by chronic heat stress during mid-pregnancy. Placental and fetal weight were measured in single bearing ewes housed either in a thermoneutral environment throughout pregnancy, or in a heated room between the 30th and 80th days of pregnancy followed by a thermone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
2
17
0
2
Order By: Relevance
“…Effects on animal production have been more extensively reviewed by Jolly [93], who described the importance of managing the thermal environments of grazing animals. Reproduction success may also be affected, with lower lambing percentages and lamb birth weight associated with elevated core body temperature [94]. For cows, this can be a decline in pregnancy rate when the average daily minimum temperature and daily THI index exceeding threshohlds [95].…”
Section: Impact Of Heat Stress On Animal Health and Productionmentioning
confidence: 99%
“…Effects on animal production have been more extensively reviewed by Jolly [93], who described the importance of managing the thermal environments of grazing animals. Reproduction success may also be affected, with lower lambing percentages and lamb birth weight associated with elevated core body temperature [94]. For cows, this can be a decline in pregnancy rate when the average daily minimum temperature and daily THI index exceeding threshohlds [95].…”
Section: Impact Of Heat Stress On Animal Health and Productionmentioning
confidence: 99%
“…The smaller lambs can be attributed to several contributing factors that occur in heatstressed ewes. Uterine blood flow decreased by 20 to 30% in heat-stressed ewes with a 1°C increase in core body temperature (Dreiling et al, 1991), and placenta weight was decreased in heat-stressed ewes at 80 and 140 d of gestation (McCrabb et al, 1993).…”
Section: Discussionmentioning
confidence: 94%
“…Respiration rate increases during periods of heat stress to utilize evaporative cooling from the membranes of the oral and nasal cavities to regulate body temperature, and the increased air movement through the respiratory system dissipates heat (Hales and Brown, 1974;Hofman and Riegle, 1977). Heat stress of ewes during pregnancy has been reported to result in smaller lambs and a decreased placental weight (Dreiling et al, 1991;McCrabb et al, 1993). In a review by Marai et al (2007), the authors cited studies that reported sweating in wool sheep is not very effective at regulating body temperature due to the wool cover.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral stressors were mainly reported to have no impact or to increase birth weight (Table 2). Heat stress during the last third of pregnancy had no impact (Shell et al, 1995) or decreased birth weight in calves, lambs and goat kids (Collier et al, 1982;McCrabb et al, 1993;Mellado et al, 2000;Tao et al, 2012). Moreover, it has been shown in ewes that heat stress during mid-pregnancy had a delayed effect on fetal growth later during pregnancy, probably because of a long-lasting negative effect on placental growth (McCrabb et al, 1993).…”
Section: Effect Of Maternal Stress During Gestation On the Biology Ofmentioning
confidence: 99%
“…Heat stress during the last third of pregnancy had no impact (Shell et al, 1995) or decreased birth weight in calves, lambs and goat kids (Collier et al, 1982;McCrabb et al, 1993;Mellado et al, 2000;Tao et al, 2012). Moreover, it has been shown in ewes that heat stress during mid-pregnancy had a delayed effect on fetal growth later during pregnancy, probably because of a long-lasting negative effect on placental growth (McCrabb et al, 1993). Exposure of dams to winter weather during the last third of gestation decreased the birth weight of calves relatively to those of dams housed at thermoneutrality (Andreoli et al, 1988).…”
Section: Effect Of Maternal Stress During Gestation On the Biology Ofmentioning
confidence: 99%